Occupational Stress and Coping Strategies Used by Secondary School Teachers in Kisumu County, Kenya - Akinyi, Mudis Pamela (Journal of Advanced Research in Education, 2025)
Although, teaching is a noble occupation, it comes with a lot of commitment and responsibilities that are highly demanding and which requires resilience to cope with stress. Teachers are predisposed to stress from lesson planning, heavy workload, strained relationships from the school administrators and colleagues as well as financial constraints, mental health issues and family work balance. Thus, the necessity to prioritize better coping strategies to help teachers manage occupational stress. This study assessed Occupational stress and coping strategies used by secondary school teachers in Kisumu County, Kenya. A mixed method research design was used in the study. Secondary school teachers in Kisumu County were the targeted population. Simple random sampling technique was used to select 100 teachers from secondary schools in Kisumu County. The data collection instruments were questionnaires and focused group discussions. Analysis of data was done through descriptive statistics and thematic analysis for the focus group discussions. Findings of the study indicate that teachers in Kisumu County are highly stressed. Results also point out that teachers use coping strategies ranging from mindfulness, religious activities, counseling, exercise, social support network, suicidal tendencies, reading, professional development, alcohol and substance abuse; some of which are unhealthy. The study recommends a counseling unit for teaching staff both at the school and county level. Teachers should also prioritize self-care for their own mental wellness. Moreover, the teacher’s welfare should be put at the heart of educational institutions through open communication channels, active and empathic listening for enhanced performance and teachers’ mental wellness.